# Pre Calculus

posted by .

Find the Derivative of F(x)=4x2(the previous 2 is squared)-2x

• Pre Calculus -

y = 4 x^2 -2 x
in general derivative of x^n = n x^(n-1) so
dy/dx = 4 * 2 x^1 - 2 x^0
which is
8 x - 2

• Pre Calculus -

Now if you have not had that relation you have to do it from the definition
dy/dx = (y at x+h - y at x) /h as h-->0
here
y at x+h = 4 (x+h)^2 - 2 (x+h)
= 4 x^2 + 8 x h +4 h^2 - 2 x - 2 h

y at x = 4 x^2 - 2 x

difference over h = 8 x + 4 h - 2
as h-->0 that is
8 x - 2

## Similar Questions

1. ### calc

derivative of (x^3/6)+(1/2x)? i got (x^2/2)-(1/2x^2) is that correct?
2. ### Calculus

Find the derivative: h(x)=7x/sqrt(5-2x) Using the chain rule...I figured out my previous post.
3. ### Algebra

Below is a "complete the square problem" from a math help site on the internet. This is the original problem. 4x2 – 2x – 5 = 0 Move the loose number over to the other side. 4x2 – 2x = 5 Divide through by whatever is multiplied …
4. ### Calculus - derivatives

Okay, I want to find the derivative of (x^x)^(x^x)... Well, I already went through the process of finding the derivative of just x^x (I used ln to do this). This is what I found... dy/dx = x^x(lnx+1) So now I want to find the derivative …
5. ### calculus

Consider the function below. f(x) = 4x2 - 5x (a) Find f '(2). (b) Use the answer in part (a) to find an equation of the tangent line to the parabola y = 4x2 - 5x at the point (2, 6). y =
6. ### pre-calculus

find the derivative of y=(3x+1)^2 y= square root 13x^2-5x+8
7. ### calculus

Construct a sign chart for the derivative. Then determine the relative and absolute extrema for y = -4x2 + 4 on the interval [-3,3].
8. ### pre cal

Factor completely: 3x^2(4x2 + 1)^8 + 64x^4(4x2 + 1)^7.
9. ### Math

Find the shortcut. Solve these problems. Then find and explain a shortcut method for finding the answer. 52(Squared) - 42 (squared) = 82 (Squared) - 72 (Squared) = 122 (Squared) - 112 (Squared) = 312 (Squared) - 302 (Squared) = 892 …
10. ### Pre cal

Fine a third degree polynomial function f(x) with real coefficients that has 4 and 2i are zeros and such that f(-1) =-50 4 21 -2i (x-4)(x-2i)(x+2i) (x-4)(x2+4) x3-16+4x-4x2 (x3-4x2+4x-16) -50=a(-1-4-4-16) -50=.25 a=2 Not understanding, …

More Similar Questions